1998
DOI: 10.1073/pnas.95.17.10009
|View full text |Cite
|
Sign up to set email alerts
|

A mutated human homologue to yeast Upf1 protein has a dominant-negative effect on the decay of nonsensecontaining mRNAs in mammalian cells

Abstract: All eukaryotic cells analyzed have developed mechanisms to eliminate the production of mRNAs that prematurely terminate translation. The mechanisms are thought to exist to protect cells from the deleterious effects of in-frame nonsense codons that are generated by routine inefficiencies and inaccuracies in RNA metabolism such as pre-mRNA splicing. Depending on the particular mRNA and how it is produced, nonsense codons can mediate a reduction in mRNA abundance either (i) before its release from an association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
142
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 175 publications
(150 citation statements)
references
References 45 publications
8
142
0
Order By: Relevance
“…The RNA-binding characteristics of HUpf1 were investigated using a gel shift assay described previously (Czaplinski et al+, 1995;Weng et al+, 1996aWeng et al+, , 1996b)+ A uniformly labeled 130-nt-long transcript generated from random sequence was used as a probe+ The ability of HUpf1 protein to bind this RNA was assayed by monitoring the mobility of the RNA probe in a native gel+ The results demonstrated that addition of HUpf1 protein retarded the mobility of the substrate RNA consistent with formation of HUpf1:RNA complexes (Fig+ 6A, lane 2)+ We next asked whether ATP addition to the reactions reduced the HUpf1:RNA complexes+ Reactions were prepared as described above and ATP was subsequently added to the mixtures+ The results demonstrated that addition of ATP to the reactions markedly reduced formation of the HUpf1:RNA complexes (Fig+ 6A, lane 3)+ Taken together, these results demon- (Sun et al+, 1998)+ These results indicate that human Upf1 is an important factor in regulating mRNA decay and translation, and understanding its biochemical activities is important for elucidating its role in NMD and translation termination+ The studies reported here describe the approach used to purify the human Upf1 protein and characterize its biochemical properties+ An epitope-tagged HUpf1 was expressed in a baculovirus expression system and was purified from extracts of insect cells infected with recombinant baculovirus particles+ Purification was achieved in a single step using immunoaffinity chromatography with a monoclonal antibody against the Flag-epitope tag inserted at the amino terminus of the protein+ The purified HUpf1 demonstrated a nucleic-acid-dependent ATPase activity that could be stimulated by several different RNA or DNA polymers (Fig+ 2)+ The ATPase assays were optimized and the results demonstrated that the ATPase activity of HUpf1 functioned best at pH 4-6, with increases in pH leading to reduced activity (Fig+ 2A)+ The ATPase activity was present over a broad range of salt concentrations (0-300 mM Analogous to the yeast Upf1p, the HUpf1 was also shown to be a helicase+ The HUpf1 was able to unwind a partially duplexed nucleic acid substrate+ The yeast Upf1p was shown to displace duplexes containing a 59 single-stranded extension (Czaplinski et al+, 1995 Understanding the biochemical activities of the yeast Upf1p has provided insight into how the Upf1p may influence translation termination and NMD (Weng et al+, 1996a(Weng et al+, , 1996b(Weng et al+, , 1998Czaplinski et al+, 1998Czaplinski et al+, , 1999)+ These results showed that ATP is an important cofactor that can modulate Upf1p RNA-binding activity (Weng et al+, 1998)+ Furthermore, the ATPase/helicase activity of the Upf1p is important for NMD, but is not required for its role in translation termination+ Considering the strong conservation of sequence and function between the yeast and human Upf1, we suggest that these activities will also be important for HUpf1 to function+ Future experiments will be performed to characterize the interactions of the human translation termination factors with the Upf1 and the consequence of these interactions on its biochemical activity+ Furthermore, additional investigations are required to understand the role of the divergent amino-and carboxyl-terminal ends of the HUpf1+ It is possible that these unique domains may be interaction domains for factors that are unique to mammalian organisms that may...…”
Section: Characterization Of Hupf1 Nucleic-acid-binding Activitymentioning
confidence: 75%
“…The RNA-binding characteristics of HUpf1 were investigated using a gel shift assay described previously (Czaplinski et al+, 1995;Weng et al+, 1996aWeng et al+, , 1996b)+ A uniformly labeled 130-nt-long transcript generated from random sequence was used as a probe+ The ability of HUpf1 protein to bind this RNA was assayed by monitoring the mobility of the RNA probe in a native gel+ The results demonstrated that addition of HUpf1 protein retarded the mobility of the substrate RNA consistent with formation of HUpf1:RNA complexes (Fig+ 6A, lane 2)+ We next asked whether ATP addition to the reactions reduced the HUpf1:RNA complexes+ Reactions were prepared as described above and ATP was subsequently added to the mixtures+ The results demonstrated that addition of ATP to the reactions markedly reduced formation of the HUpf1:RNA complexes (Fig+ 6A, lane 3)+ Taken together, these results demon- (Sun et al+, 1998)+ These results indicate that human Upf1 is an important factor in regulating mRNA decay and translation, and understanding its biochemical activities is important for elucidating its role in NMD and translation termination+ The studies reported here describe the approach used to purify the human Upf1 protein and characterize its biochemical properties+ An epitope-tagged HUpf1 was expressed in a baculovirus expression system and was purified from extracts of insect cells infected with recombinant baculovirus particles+ Purification was achieved in a single step using immunoaffinity chromatography with a monoclonal antibody against the Flag-epitope tag inserted at the amino terminus of the protein+ The purified HUpf1 demonstrated a nucleic-acid-dependent ATPase activity that could be stimulated by several different RNA or DNA polymers (Fig+ 2)+ The ATPase assays were optimized and the results demonstrated that the ATPase activity of HUpf1 functioned best at pH 4-6, with increases in pH leading to reduced activity (Fig+ 2A)+ The ATPase activity was present over a broad range of salt concentrations (0-300 mM Analogous to the yeast Upf1p, the HUpf1 was also shown to be a helicase+ The HUpf1 was able to unwind a partially duplexed nucleic acid substrate+ The yeast Upf1p was shown to displace duplexes containing a 59 single-stranded extension (Czaplinski et al+, 1995 Understanding the biochemical activities of the yeast Upf1p has provided insight into how the Upf1p may influence translation termination and NMD (Weng et al+, 1996a(Weng et al+, , 1996b(Weng et al+, , 1998Czaplinski et al+, 1998Czaplinski et al+, , 1999)+ These results showed that ATP is an important cofactor that can modulate Upf1p RNA-binding activity (Weng et al+, 1998)+ Furthermore, the ATPase/helicase activity of the Upf1p is important for NMD, but is not required for its role in translation termination+ Considering the strong conservation of sequence and function between the yeast and human Upf1, we suggest that these activities will also be important for HUpf1 to function+ Future experiments will be performed to characterize the interactions of the human translation termination factors with the Upf1 and the consequence of these interactions on its biochemical activity+ Furthermore, additional investigations are required to understand the role of the divergent amino-and carboxyl-terminal ends of the HUpf1+ It is possible that these unique domains may be interaction domains for factors that are unique to mammalian organisms that may...…”
Section: Characterization Of Hupf1 Nucleic-acid-binding Activitymentioning
confidence: 75%
“…Second, Se concentration affected only the level of UGA(72)-containing mRNA. Third, the level of UGA(72)-containing mRNA, like UAA(72)-containing mRNA but not UGU(72)-containing mRNA, was increased by the expression of a dominant-negative form of hUpf1 protein (Figure 4), which is known to abrogate NMD (Sun et al, 1998). We conclude that PHGPx mRNA that derives from a full-length gene contains all of the cis-acting sequences required to support NMD.…”
Section: Discussionmentioning
confidence: 87%
“…Each nonsense codon resulted in a reduction in mRNA abundance (Figure 3). In keeping with the idea that the reduction in abundance is a reflection of NMD, overexpression of a dominant-negative (R844C) form of human (h) Upf1 protein (Sun et al, 1998) increased the levels of PHGPx mRNA harboring either UGA(72) or UAA(72) approximately twofold but had no effect on the level of PHGPx mRNA harboring UGU(72), whereas overexpression of a wild-type (Wt) form of hUpf1 protein had no effect on the level of any of the three mRNAs (Figure 4).One possible explanation for the failure of the transient transfections to recapitulate the metabolism of PHGPx RNA observed for rat liver and testis could be that the transfections were performed with an incomplete PHGPx gene. To .…”
mentioning
confidence: 99%
“…This pathway can modulate phenotypes arising from nonsense or frameshift mutations, but little is known about the physiologic role of NMD in higher eukaryotes. To address this issue, we examined expression profiles in mammalian cells depleted of Rent1 (also called hUpf1), a factor essential for NMD 3,4 . Upregulated transcripts included those with upstream open reading frames in the 5¢ untranslated region, alternative splicing that introduces nonsense codons or frameshifts, introns in the 3¢ untranslated region or selenocysteine codons.…”
mentioning
confidence: 99%